Management of Blood Glucose Levels in Type 2 Diabetes Mellitus Patients Through Ramadan Fasting: a Literature Review: Manajemen Kadar Glukosa Darah Pasien Diabetes Mellitus Tipe 2 Melalui Puasa Ramadhan: Literatur Review - Agustin, Leony Delvechia; Istiqomah, Indriana Noor; Mashuri (Al-Hijrah Indonesia, 2022)
Diabetes Mellitus causes about 5% of deaths from all total deaths in the world due to lack of self care in DM patients, causing instability of blood glucose levels that cause acute and chronic complications. Nurses have a role in overcoming the instability of blood glucose levels by performing the main intervention, namely hyperglycemia management. From these interventions, Ramadan fasting is a safe dietary choice for patients with type 2 diabetes. This study uses a literature review method with article searches conducted on the PubMed electronic database, Science Direct, and Open Knowledge Maps. The results of the literature review show that the length of Ramadan fasting carried out by participants from all journals is 30 days, with a fasting duration of 10-15 hours/day. Blood sugar levels of type 2 DM participants after Ramadan fasting showed a decrease of 4-43.33 mg/dl, and 1.81-3.01 mmol/L, and the HbA1c value decreased by 0.21-2.2%. The results of statistical tests showed that fasting during Ramadan was quite effective in reducing KGD/HbA1c with a p value of < 0.05. This literature review concludes that Ramadan fasting is effective in reducing blood glucose levels in type 2 DM patients and the practice still conforms to the International Diabetes Federation – Diabetes And Ramadan (IDF-DAR) guidelines.